PEMAHAMAN ANGGOTA GEREJA MASEHI ADVENT HARI KETUJUH TERHADAP PERATURAN DAN PENDISIPLINAN ANGGOTA YANG BERSALAH BERDASARKAN MATIUS 18:15-18 DI WILAYAH XII KONFERENS DKI JAKARTA DAN SEKITARNYA - Marbun, Ucok Steven; Hendriks, Alvyn (Jurnal Marturia, 2017)
This thesis begins with explanation about background of The Understanding Of Seventh Day Adventist Church Member About The Rule And Discipline For The Guilty Church Member According To Matthew 18 : 15-18 In Region XII Of Jakarta Conference And Vinicity. The key words are: Rule and Discipline. The discussion about The Rule and Discipline for Church Member is very relevant for the church’s condition nowadays, because there are many churches or church members are separated because of not applying the rule and discipline inside the church. Nowadays the churches rarely monitor, warn and guide the sinned member to repent and being back to God. Even the church that hardly maintain in submitting or telling God’s words faithfully often get weak in applying the discipline or punishment. Those kinds of church generally give reason that applying discipline inside the church will bring the bad consequences or result for the members who did mistakes, they will be offended and leave the church. Some people think that there’s no strong reason to punish someone just because doing a little sin, particularly if the mistaken one is a well known, rich and powerful church member. The church is not willing to punish or apply discipline for them because of worrying they will move to other church. The important of applying rule and discipline is to be a tool for improving the spirituality growth so it will motivate the other church member to pay attention to reprimanded or warn “them that are unruly, comfort the feebleminded, support the weak, be patient toward all men” (1 Thessalonians 5:14). So, the purpose of applying discipline is:Â First, saving the church (1 Corinthians 5:5). Second, saving the sinner (1 Corinthians 5:2, 5). Jesus gave the method to reprimand or warn the mistaken persons or those who doesn’t obey God’s command, in Matthew 18:15 18 is written the concrete rules about herding especially for the guilty or mistaken member. By :Â First, reprimanding or warning to make every one responsible for each other (1 Thessalonians 5:11, 14 it’s edify or admonish, esteeming and comfort each other). Second, eyes to eyes means without any witness, for reaching back our guilty brothers. Third, two or three people, if the second way doesn’t succeed, we may ask one or two more people as witnesses. Here, the witness is for “discussion partner”, which means a person who helps the discussion to run well with the brotherhood spirit of solidarity. Fourth, if the reprimanding or warning with the witnesses doesn’t succeed, bring the problem to all the church member / church. Fifth, look at the mistaken person as a person who doesn’t know about God, this means, the person should be considered as an unbeliever and he should be excommunicated. But it doesn’t mean we should excommunicated all of his life, we should keep praying for him because the purpose of applying discipline or punishment is not to destroy his faith but to make him back to God. The research was conducted at Seventh Day Adventist Churches In Region XII Of Jakarta Conference And Vinicity, with purpose is to know how far the understanding of the church members about the important of the rule and discipline for the guilty / mistaken member, and how far the church members and elders understand that the base or foundation of the rule and discipline is actually God’s Love to keep the holiness of God’s church and also how many member who applies the rule and discipline well to improve the church’s growth. The method that was used for this research is quantitative, and the tool that was used to collect data is questionnaire to measure The Understanding Of Seventh Day Adventist Church Member About The Rule And Discipline For The Guilty Church Member According To Matthew 18 : 15-18 In Region XII Of Jakarta Conference And Vinicity. The result of research shows that “Rule and Discipline Improve The Spirituality” (X1), toward “Rule and Discipline is The Reflection of God’s Love” (X2), toward “Giving Advice and Reprimanded Well” (X3), the conclusion and abstract of this thesis, writer will present the result of research analysis as a reality from respondents’ answer, the application is presented in three (3) parts as follows: The survey result from 150 respondents who answered each question onÂ the questionnaire, founded that the lowest understanding is at question number 10 with average score 3.48, it means that many church members haven’t understood yet about the importance of rule and discipline for the guilty member. This thing should be a serious attention through the role of Pastor and elders of the church to motivate every church member for the spirituality growth in God’s way. The result of research also presents that from all the variables as follow: First, Rule and Discipline Improve Spirituality, it gave score toward the questionnaire which point is 3.99. It means entirely, the average respondent agree that Rule and Discipline Improve Spirituality. Second, Rule and Discipline is the reflection of God’s Love, it gave score toward questionnaire which point is 3.96. It means entirely, the average respondent agree that Rule and Discipline is the reflection of God’s Love. Third, Giving Advice and Reprimanded Well, it gave score toward questionnaire which point is 4.16. It means entirely, the average respondent agree for Giving Advice and Reprimanded Well. So we may conclude that The Understanding Of Seventh Day Adventist Church Member About The Rule And Discipline For The Guilty Church Member According To Matthew 18 : 15-18 In Region XII Of Jakarta Conference And Vinicity, with total average score is 4.03, it means that they agree that Understanding Of Seventh Day Adventist Church Member About The Rule And Discipline For The Guilty Church Member According To Matthew 18 : 15-18 In Region XII Of Jakarta Conference And Vinicity.Â The last part is a conclusion of research analyst from field research, implication and suggestion which can be applied for every church member to understand the importance of the rule and discipline for the guilty member for the spirituality growth.